Impact of lattice vibrations on equation of state of the hardest boron phase - Isaev, Eyvaz; Simak, S. I.; Mikhaylushkin, A. S.; Vekilov, Yu. Kh.; Zarechnaya, E. Yu.; Dubrovinsky, L.; Dubrovinskaia, Natalia; Merlini, M.; Hanfland, M.; Abrikosov, I. A. (Physical review. B, Condensed matter and materials physics, 2011)
An accurate equation of state (EOS) is determined for the high-pressure orthorhombic phase of boron, B28, experimentally as well as from ab initio calculations. The unique feature of our experiment is that it is carried out on the single crystal of B28. In theory, we take into consideration the lattice vibrations, often neglected in first-principles simulations. We show that the phonon contribution has a profound effect on the EOS of B28, giving rise to anomalously low values of the pressure derivative of the bulk modulus and greatly improving the agreement between theory and experiment.
Gesehen am 04.07.2022